(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2026)
Functional textile are one of the most critical fields in the textile industry and textile materials science. In recent years, advanced technologies in textile processing have become relevant in order to improve its usability. In the production of various types of functional textile, one of the methods is the modification of textile surfaces. To improve the properties of the textile surface, magnetron vacuum sputtering and laser post-processing technologies can be used, which in general gives the material new or improved properties and functionalities. In this study, mixed fiber fabrics containing polyester, protal and cotton fibers are used to determine how laser post-treatment of the metalized fabrics impact the adhesive properties between fabric and deposited metal. The following materials were used for magnetron vacuum sputtering for functional textile coatings: Cu, Al, Ti, Ag. Individually or by combining these metals, it is possible to assign the textile such properties as: electromagnetic, UV and IR radiation shielding; antistatic, antibacterial, hydrophilic and hydrophobic properties, as well as increasing wear resistance. In this study a 100 W continuous wave CO2 laser with a wavelength of 10.6 µm is used for post-treatment of magnetron vacuum sputtered modified textile surfaces. The study's conclusions point towards a tailored approach in determining linear energy densities that bolster adhesion for each metal-textile combination, which is essential for the development of durable and functional advanced textile. The patterns noted in the adhesion strengths, influenced by different energy densities and metal types, highlight the intricate relationship between the thermal impact of laser treatment and the inherent characteristics of the metals deposited. Some metals demonstrated improved adhesion at lower energy densities. However, a general trend emerged showing a reduction in the strength of adhesion as the energy density increased, especially when surpassing certain energy levels.